Histopathology of Rats Intestinal Treated with High-Fat Diet and Neem Leaf Extract - Azmi Syafanah Nur Hasna; Sri Isdadiyanto; Agung Janika Sitasiwi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The high-fat diet can increase free radicals, which can damage the intestinal histological structure. The ethanolic neem leaf extract contains antioxidants that have the potential to help improve the intestinal histological structure. This study aims to examine the effectiveness of ethanolic neem (A. indica A. Juss) leaf extract on the histopathological structure of the small intestine in rats (R. norvegicus L.) hyperlipidemia. This study used 24 rats divided into 6 groups: normal control, positive control, high-fat diet + simvastatin, the test groups dose I, II, and III (ethanolic neem leaf extract 75 mg/200 gBW, 100 mg/200 gBW, and 125 mg/200 gBW). The results of the analysis using ANOVA test on the height of villi, mucous thickness, and number of goblet cells in the small intestine part duodenum, jejunum, and ileum showed no significant difference (p>0.05). The results of the morphology of epithelial cells in treatments P0, P2, and P5 showed normal epithelial cells, whereas treatments P1, P3, and P4 showed erosion epithelial cells. Based on the result, the ethanolic neem (A. indica A. Juss) leaf extract can suppress the damage effects of epithelial cells and the histological structure of the small intestine in rats (R. norvegicus L.) hyperlipidemia